El redescubrimiento de Serjania dura Radlk. (Sapindaceae) en Brasil - Ferrucci, María Silvia; Somner, Genise Viera (Revista de Biologia Neotropical / Journal of Neotropical Biology, 2007)
The rediscovery of Serjania dura Radlk. (Sapindaceae-Paullinieae), taxon described for Brazil, pre vio usly kno wn only a flowerin g specimen la ckin g cole ction date and lo cality . It i s here fully de scri bed, illustrated, and compared with S. gracilis Radlk., a closely related species.